A pathologically proven case of adult-onset HIV-related lymphocytic interstitial pneumonia with acute exacerbation treated with steroid and antiretroviral therapy. Issue 12 (December 2015) - Saito, Makoto; Hatakeyama, Shuji; Wakabayashi, Yoshitaka; Yanagimoto, Shintaro; Takemura, Tamiko; Yotsuyanagi, Hiroshi
Abstract: Lymphocytic interstitial pneumonia (LIP) is a rare opportunistic illness in human immunodeficiency virus (HIV)-infected adults, although it is relatively common among HIV-infected children. Most adult cases have been reported in African and Afro-Caribbean patients and few cases have been reported from Asia. Acute exacerbation of HIV-related LIP has not been well described. Here we report a pathologically proven case of acute exacerbation of adult-onset HIV-related LIP. The patient was an African immigrant living in Japan who presented with chronic dyspnea and diffuse bilateral pulmonary infiltrates. His clinical, radiological, and pathological findings were consistent with those of LIP. After a diagnostic surgical lung biopsy, his hypoxemia and pulmonary infiltrates exacerbated rapidly over a few days, although his condition had not progressed during the previous year. LIP may be an important differential diagnosis among adult patients in Asian countries, especially patients of non-Asian ethnicity.